Fiber spray ionization mass spectrometry in forensic chemistry: A screening of drugs of abuse and direct determination of cocaine in urine. (10th May 2020) - Filho, João Francisco Allochio; dos Santos, Nayara A.; Borges, Keyller Bastos; Lacerda, Valdemar; Pelição, Fabrício Souza; Romão, Wanderson
Abstract : Rationale: Ambient mass spectrometry techniques are much required in forensic chemistry to evaluate evidence with low analytical interference, high confidence, and accuracy. However, traditional methodologies, such as paper spray ionization, have been shown to present low sensitivity in the analysis of illicit drugs from biological matrices. Methods: Fiber spray ionization mass spectrometry (FSI‐MS) was developed using a capillary polypropylene (PP) hollow fiber. Seized samples of drugs, i.e. a tablet, blotter paper, hashish, and cocaine powder, were analyzed. Cocaine was quantified from whole urine by dipping the fiber directly into solution. FSI‐MS was tested for the analysis of a sample of urine obtained from a drug abuse suspect. Results: The FSI(+) analysis showed the detection of different types of synthetic drugs in tablet and blotter paper samples, e.g. amphetamine, cathinones, phenethylamines, and opioids, while pure cocaine and different types of coca alkaloids were identified from cocaine powder with good sensitivity and high mass accuracy. The hashish analysis by FSI(−) revealed signals of cannabinoids, cannabinoid acids, and cannabinoid derivatives, detected mainly as [M − H] − ions or chlorine adducts [M + Cl] − . The quantification of cocaine in whole urine showed good sensitivity and precision with limits of detection and quantification of 5.16 and 17.21 ng/mL, respectively, linearity above 0.999, and relative standard deviation below 2.71%. The evaluation of seized sample of urine showed the detection of cocaine with relative ion intensity greater than 36%, as well as the metabolites benzoylecgonine and cocaethylene with a relative intensity of 1.4% and 6%, respectively. Conclusions: The developed FSI‐MS method has the potential to be applied to forensic sample evaluation as well as to determine illicit drugs from biological matrices in toxicological analysis. The use of a capillary PP fiber has advantages as an extractor agent and ionizing substrate, and also the feature of it being dipped directly into the sample, thus preserving the integrity of the sample, which makes this a very promising ambient mass spectrometry method and relevant to forensic chemistry.